« In the presence of absence » : la remémoration dans The Conjugial Angel d’A. S. Byatt - Camille Fort (Études Britanniques Contemporaines, 2005)
This article attempts a reading of A. S. Byatt’s novella, which exploits a historical and literary heritage (Alfred and Emily Tennyson’s dual effort to mourn Arthur Hallam) so as to question the relationship between mourning and writing. In Memoriam, Alfred’s elegiac poem, frames writing within an masculine order of mourning which is opposed to the female characters’ spiritual meetings. The women succeed in « voicing » the text till it achieves a present enunciation through the figure of the Angel and his unmediated speech. Memory becomes a way of producing disordered, affect-laden images, reminding us that the post-modern novel finds its vocation half-way between archive and performance. Rememoration can no longer be confused with re-membering (its function according to the Victorian characters in the novel) : its expressive potential is brought forth as it effects discursive fragmentation.